2000
DOI: 10.1046/j.1523-1755.2000.00871.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of γ glutamyl transpeptidase to oxidative damage of ischemic rat kidney

Abstract: Ex vivo data supporting a net pro-oxidant effect of up-regulated GGT during short-term ischemia of rat kidney have been obtained. The enzyme stimulation appears to contribute to the renal morphological damage exerted by a brief hypoxic condition at the level of PT cells. The actual impact on kidney function by GGT-dependent oxidative damage during transient ischemia and the potential protective action of GGT inhibitors require subsequent investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 34 publications
1
17
1
1
Order By: Relevance
“…Previous studies have demonstrated that acivicin has a protective effect on cisplatin-induced nephrotoxicity (Hanigan et al, 1994) and suppresses GGT-dependent oxidative damage in ischemic rat kidney (Cutrín et al, 2000). However, acivicin is known to inhibit irreversibly various glutamine amidotransferases, including imidazole glycerol phosphate synthase and guanine monophosphate synthetase, and inactivate a number of biosynthetic enzymes for purine and pyrimidine, amino acids, and amino sugars, which results in a potent cytotoxicity (Earhart and Neil, 1985;Chittur et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that acivicin has a protective effect on cisplatin-induced nephrotoxicity (Hanigan et al, 1994) and suppresses GGT-dependent oxidative damage in ischemic rat kidney (Cutrín et al, 2000). However, acivicin is known to inhibit irreversibly various glutamine amidotransferases, including imidazole glycerol phosphate synthase and guanine monophosphate synthetase, and inactivate a number of biosynthetic enzymes for purine and pyrimidine, amino acids, and amino sugars, which results in a potent cytotoxicity (Earhart and Neil, 1985;Chittur et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, it still remains to be elucidated whether these interventions are also beneficial in clinical cases. Cutrín et al (2000) have reported that short-term kidney ischemia (25 min) increases GGT activity and also enhances lipid peroxidation, suggesting that the postischemic AKI is related to an increase of GGT activity. In fact, acivicin, a prototype of GGT inhibitor (Capraro and Hughey, 1985), could prevent the ischemia-induced increase in GGT activity, lipid peroxidation enhancement, and morphological alterations (Curtin et al, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Opinion on whether serum uric acid is a true risk factor for mortality and cardiovascular disease, or is simply associated with other risk factors, is divided, but there is no doubt that it is associated with the metabolic syndrome (Liese et al, 1999;Tomita et al, 2000). Serum gammaglutamyl transferase (GGT) has been shown to be prospectively associated with cardiovascular disease (Cutrin et al, 2000;Emdin et al, 2001;Hood et al, 1990;Lee et al, 2006;Pompella et al, 2004;Ruttmann et al, 2005;Wannamethee et al, 1995), hypertension (Lee et al, 2003b;Miura et al, 1994) and diabetes (Lee et al, 2003a;Lee et al, 2003b;Lee et al, 2004;Meisinger et al, 2005;Nakanishi et al, 2003;Perry et al, 1998;Wannamethee et al, 2005;Whitfield, 2001). Serum GGT is significantly correlated with total or LDL cholesterol, high-density lipoprotein (inversely), and particularly with triglycerides (Whitfield, 2001;Whitfield et al, 2002).…”
mentioning
confidence: 99%
“…Aviacin (an inhibitor of GGT) prevented the increase of GGT activity induced by ischemia and protected the ischemic organs and tissues against lipid peroxidation, free radical generation and morphological changes. [15].…”
Section: Discussionmentioning
confidence: 99%